Cytotoxic effects of ivermectin on Giardia lamblia: induction of apoptosis and cell cycle arrest - Barzola, Florencia Nicole; Laiolo, Jerónimo; Cotelo, Camilo; Joray, Mariana Belén; Volpini, Ximena; Rivero, María Romina; Rópolo, Andrea Silvana; Touz, María Carolina; Feliziani, Constanza (Frontiers in Microbiology, 2024)
IntroductionGiardia lamblia is a flagellated protozoan parasite causing giardiasis, a common intestinal infection characterized by diarrhea, abdominal cramps, and nausea. Treatments employed to combat this parasitic infection have remained unchanged for the past 40 years, leading to the emergence of resistant strains and prompting the search for new therapeutic agents.MethodsThis study investigated the cytotoxic effects of ivermectin (IVM) on G. lamblia trophozoites. We conducted dose-response experiments to assess IVM-induced cytotoxicity. We utilized various biochemical and ultrastructural analyses to explore the underlying mechanisms of cell death, including reactive oxygen species (ROS) production, DNA fragmentation, cell cycle arrest, and apoptosis markers.ResultsOur findings demonstrate that IVM induces dose-dependent cytotoxicity and triggers cell death pathways. We found that IVM treatment generates elevated levels of reactive oxygen species (ROS), DNA fragmentation, and arrests of trophozoites in the cell cycle’s S phase. Additionally, ultrastructural analysis reveals morphological alterations consistent with apoptosis, such as cytoplasmic vacuolization, chromatin condensation, and tubulin distribution.DiscussionThe insights gained from this study may contribute to developing new therapeutic strategies against giardiasis, addressing the challenge posed by drug-resistant strains.